Downy mildew management in protected cultivation of table grapes 'BRS Clara' - Genta, Werner; Tessmann, Dauri José; Roberto, Sérgio Ruffo; Vida, João Batista; Colombo, Larissa Abgariani; Scapin, Claudia Regina; Ricce, Willian da Silva; Clovis, Luiz Rafael (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the efficiency of plastic cover and plastic shade screen, associated or not with fungicide spray programs, for downy mildew control in 'BRS Clara' table grapes in the first and second growing seasons in Northern Paraná State, and to analyze the influence of microclimatic variables on disease progress. The first and the second growing seasons assessed were from September to December and from January to May, respectively. The experiments were carriet out twice in two growing seasons – September to December, and January to May – in 2008 and 2009. The experimental design was a randomized block with seven treatments and four replicates. The following treatments were compared: plastic shade screen without fungicides for controlling downy mildew, or plastic shade with fungicides applied according to conventional standards; plastic cover without fungicide or with powdery mildew fungicides only; plastic cover with 25% or 50% of fungicides specified by conventional standards; and plastic cover with phosphite and copper fungicides. The plastic cover allows to reduce the number of fungicide applications required to control downy mildew up to 75%, in comparison to the plastic shade screen. The disease severity has a high positive correlation with the duration of leaf wetness and with the air relative humidity higher than 90%. Under the plastic shade screen, severity is also highly correlated with the amount of rainfall.